APPLICATION OF THEMATIC LEARNING BASED ON OBSERVATION OF STUDY CLAUSES IN SD NEGERI 14 BANDA ACEH - Fifta Maulisyah; Uswatul Hasanah; Zatil Yumna; Tiya Ramayanti; Dr. Siti Mayang Sari, M.Pd (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research uses a descriptive qualitative research method, namely research based on phenomena that occurred in one case at SD Negeri 14 Banda Aceh. Based on the facts seen in the school, teachers still use old/conventional methods in the thematic learning process. Researchers observed the learning carried out by teachers at SD Negeri 14 Banda Aceh, that thematic learning really provided opportunities for teacher creativity in the active learning process. Through this research method, it will be explained transparently to produce the application of integrative thematic learning using a causal study. It is known that the curriculum used in this school is still some classes using the independent learning curriculum so that the learning process carried out is quite different and not significant to the results obtained by students in integrative thematic learning. Based on the research results, SD Negeri 14 Banda Aceh has implemented integrative thematic-based learning from K-13 until now the Merdeka Curriculum. Integrative thematic learning that combines several subjects into one aims to make students more active and creative and improve critical thinking skills.